2013
DOI: 10.1038/ajg.2013.111
|View full text |Cite
|
Sign up to set email alerts
|

Oral Nucleoside/Nucleotide Analogs Without Hepatitis B Immune Globulin After Liver Transplantation for Hepatitis B

Abstract: Oral nucleoside/nucleotide analogs without HBIG are effective in preventing graft loss secondary to hepatitis B recurrence after liver transplantation. However, new agents with a high barrier to resistance should be used to minimize drug resistance and to prevent virological rebound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 14 publications
2
82
0
7
Order By: Relevance
“…Of two studies (14,15) from one center in China with overlapping study periods, only the latest one (14) was included in the analysis. Moreover, there were two other studies (20,24) from another center in China with overlapping study periods, but we decided to include the oldest one (20), which was published as full paper, because it provided more details on antiviral prophylaxis. Finally, one study, which was published only as an abstract, was excluded because it did not provide separate data on HBV recurrence under hgbNA(s) (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of two studies (14,15) from one center in China with overlapping study periods, only the latest one (14) was included in the analysis. Moreover, there were two other studies (20,24) from another center in China with overlapping study periods, but we decided to include the oldest one (20), which was published as full paper, because it provided more details on antiviral prophylaxis. Finally, one study, which was published only as an abstract, was excluded because it did not provide separate data on HBV recurrence under hgbNA(s) (26).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 94 articles were initially identified from the literature search, but only 20 studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) fulfilled the inclusion criteria ( Figure A1). Of two studies (14,15) from one center in China with overlapping study periods, only the latest one (14) was included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of recurrence after LT was 0%. Similarly, entecavir, Telbivudine monotherapy [78,[88][89][90][91] pre-and post LT resulted in 0% to 8% HBV recurrence rate (Table 2). Only one study found a relatively high rate of recurrent HBV infection (22.5%) using ENT [91] (Table 3).…”
Section: Anti-hbs Target Levelsmentioning
confidence: 99%
“…Since then, studies have also demonstrated the efficacy of using lower doses, and also replacing HBIG with combination oral antiviral therapy [70,71] . With the introduction of more potent NAs with minimal drug resistance, oral antiviral therapy alone without HBIG has also been shown to be highly effective in preventing graft hepatitis together with excellent long-term outcome [72][73][74][75] .…”
Section: Antiviral Therapy For Hcc Patients Undergoing Liver Transplamentioning
confidence: 99%